2015
DOI: 10.1007/s10886-015-0646-y
|View full text |Cite
|
Sign up to set email alerts
|

Emission Timetable and Quantitative Patterns of Wound-Induced Volatiles Across Different Leaf Damage Treatments in Aspen (Populus Tremula)

Abstract: Plant-feeding herbivores can generate complex patterns of foliar wounding, but it is unclear how wounding-elicited volatile emissions scale with the severity of different wounding types, and there is no common protocol for wounding experiments. We investigated the rapid initial response to wounding damage generated by different numbers of straight cuts and punctures through leaf lamina as well as varying area of lamina squeezing in the temperate deciduous tree Populus tremula Wounding-induced volatile emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
108
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(117 citation statements)
references
References 61 publications
(100 reference statements)
8
108
1
Order By: Relevance
“…In order to minimize the influence of leaf damage on VOC emissions, at least 2 days were allowed for recovery before conducting measurements. According to previous measurements, the effect of lamina wounding is short‐lived with the bulk of the stress volatiles released within first 5–10 min after wounding (Portillo‐Estrada, Kazantsev, Talts, Tosens, & Niinemets, ). We also did not observe any subsequent induction of stress volatiles and volatile isoprenoids after wounding, and leaf photosynthesis measurements with a clip‐on type gas‐exchange system (GFS‐3000, Walz GmbH, Effeltrich, Germany) demonstrated that the wounding also did not alter foliage photosynthesis rate and stomatal conductance at 48 hr since wounding stress (data not shown).…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…In order to minimize the influence of leaf damage on VOC emissions, at least 2 days were allowed for recovery before conducting measurements. According to previous measurements, the effect of lamina wounding is short‐lived with the bulk of the stress volatiles released within first 5–10 min after wounding (Portillo‐Estrada, Kazantsev, Talts, Tosens, & Niinemets, ). We also did not observe any subsequent induction of stress volatiles and volatile isoprenoids after wounding, and leaf photosynthesis measurements with a clip‐on type gas‐exchange system (GFS‐3000, Walz GmbH, Effeltrich, Germany) demonstrated that the wounding also did not alter foliage photosynthesis rate and stomatal conductance at 48 hr since wounding stress (data not shown).…”
Section: Methodsmentioning
confidence: 85%
“…The main advantages of PTR‐TOF‐MS are simultaneous detection of all masses rather than predetermined masses, higher sensitivity, higher mass resolution, and improved accuracy over the traditional quadrupole PTR (PTR‐QMS); this allows quantification of a larger number of organic compounds at trace levels in real time (Graus, Müller, & Hansel, ; Jordan et al, ). The PTR‐TOF‐MS was operated according to the method described in detail in Graus et al (), Brilli et al () and Portillo‐Estrada et al (). The drift tube voltage was kept at 600 V at 2.3 mbar drift pressure and 60°C temperature, corresponding to an E/N ≈ 130 Td in H 3 O + reagent ion mode.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the effect was not visible in the surrounding intact leaves, the damage‐triggered change in isoprene emission seems to be a leaf‐level response. Contrary to our results, previous studies have found a reduction in isoprene emission immediately after leaf damage (Loreto & Sharkey, ; Portillo‐Estrada et al ., ; Copolovici et al ., ; but see Ferrieri et al ., ). VOC emission profile emitted immediately after damage can substantially differ from longer‐term emissions (Maja et al ., ).…”
Section: Discussionmentioning
confidence: 99%